Nuclear Balance: Spread and Deterrence - Otegulov, О.Ж.; Bulegenova, Б.Б.; Sheryazdanova, Г.Р. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2019)
This article examines the current situations of nuclear weapon and its political and social influences. So far, there have been few studies in the scientific works that have been made in the country, with some research on nuclear weapons. This article analyzes the proliferation and proliferation of nuclear weapons, which are considered to be a weapon in the world, and relationships between nuclear-armed states. At present, more than 10 countries are in the world, and the state is trying to achieve this type of weapon. This can be regarded as a major threat to the world security. The refusal by Kazakhstan to abandon its nuclear arsenal as a state that was heavily damaged by nuclear tests has contributed to peace in the world. Kazakhstan will continue to pursue its policy of nuclear disarmament. However, it is very difficult for states with nuclear weapons to abandon their weapons. In this article, we will deal with nuclear weapons issues. Therefore, we hope that this article will help to compensate for the problem.